N,N-Dimethyl-N′,N′′-diphenylphosphoric triamide - Mehrdad Pourayoubi; Mohammad Yousefi; Farnaz Eslami; Arnold L. Rheingold; Chao Chen (Acta Crystallographica Section E, 2011)
In the title compound, C14H18N3OP, a crystallographic mirror plane bisects the molecule (the C,N,C atoms of the dimethylamido moiety and the P=O unit lie on the mirror plane). The P atom has a distorted tetrahedral geometry; the bond angles at P are in the range 98.98 (11)–115.28 (7)°. In the crystal, the O atom of the P=O group acts as a double hydrogen-bond acceptor for two symmetry-equivalent N—H...O hydrogen bonds, building [001] chains containing R21(6) loops.